Розвиток адміністративно-правового регулювання в галузі авіаційного транспорту - Брусакова, О. В.; Brusakova, O. V.; Оксана Брусакова (Прикарпатський юридичний вісник. - 2017. - Вип. 1 (16), т. 4. - С. 94-99, 2017)
Наголошено на важливості розвитку адміністративно-правового регулювання у сфері авіаційного транспорту. Підзаконні нормативно-правові акти, які складають основу адміністративно-правового регулювання в галузі авіаційного транспорту, на сьогодні можуть бути охарактеризовані рядом недоліків: прийняті на виконання вже не чинних нормативно-правових актів; відсилають до нечинних нормативно-правових актів; вказують на повноваження ліквідованих, реорганізованих органів влади; здійснюють нормативно-правову регламентацію не існуючих суспільних відносин; тощо. Більшість із таких актів морально застаріла, внаслідок чого потребує свого перегляду, що може бути здійснено шляхом проведення їх систематизації.

In the article it has been emphasized the importance of developing administrative and legal regulation in the field of aviation transport. The author has defined the shortcomings of administrative and legal regulation in the field of aviation transport. Namely, the by-laws, which form the basis of administrative and legal regulation in the field of aviation transport, can today be characterized by a number of shortcomings: those adopted for the implementation of no longer valid regulatory acts; refer to invalid regulatory acts; indicate the authority of the liquidated, reorganized authorities; carry out regulatory regulation of non-existent public relations; etc. It has been offered the basic directions of development of administrative and legal regulation in the field of aviation transport. In particular, the systematization of the legislation on the basis of which the administrative and legal regulation in the field of aviation is carried out should be carried out taking into account the following aspects: first of all, the secondary legislation adopted before 2011; should be reviewed; translate their provisions into the state language in full; to concentrate in the provisions of a single legal act on defining the essence of all terminology and disclosing the content of generally accepted abbreviations; remove references to invalid laws and non-existing entities. At the same time, it is necessary to recognize that the normative legal acts have lost their validity: the provisions of which are entirely devoted to the legal status of non-existent entities responsible for the implementation of administrative and legal regulation in the field of aviation transport; that they were adopted with excess of authority by the subjects of their publication and failure to comply with statutory procedures; which regulate social relations not envisaged by an act of greater legal force. As a result of such systematization, significant changes will be made to the existing ones and new regulatory acts will be adopted, which, if the above aspects are fully taken into account, will be a clear evidence of the development of administrative and legal regulation in the field of aviation transport.

Отмечена важность развития административно-правового регулирования в сфере авиационного транспорта. Подзаконные нормативно-правовые акты, составляющие основу административно-правового регулирования в области авиационного транспорта, на сегодняшний день могут быть охарактеризованы рядом недостатков: приняты во исполнение уже не действующих нормативно-правовых актов; отсылают в недействующие нормативно-правовые акты; указывают полномочия ликвидированных, реорганизованных органов власти; осуществляют нормативно правовую регламентацию не существующих общественных отношений; тому подобное. Большинство из таких актов морально устарели, вследствие чего требует своего пересмотра, что может быть осуществлено путем их систематизации.
Development of administrative and legal regulation in the field of air transport
Развитие административно-правового регулирования в области авиационного транспорта
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; авіаційний транспорт; air transport; авиационный транспорт; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование; нормативно-правові акти; normative legal acts; нормативно-правовые акты; систематизація; systematization; систематизация